Resistência de porta-enxertos de cucurbitáceas a nematóides e compatibilidade da enxertia em melão - Ito, Letícia Akemi [UNESP]; Gaion, Lucas Aparecido [UNESP]; Galatti, Francine de Souza [UNESP]; Braz, Leila Trevisan [UNESP]; Santos, Jaime Maia dos [UNESP] (Assoc Brasileira Horticultura, 2014)
Nematodes severely attack net melon plants under protected cultivation conditions. The objective of this research was to select rootstocks with resistance to Meloidogyne incognita and M. javanica. The experiment was carried out under greenhouse conditions from October 2010 to April 2011 in Jaboticabal, Sao Paulo state, Brazil. Thirty-three cucurbitaceous genotypes were investigated as rootstocks; melons: CNPH 01-930 (Cucumis melo var. flexuosus), CNPH 01-962, 01-963 CNPH (Cucumis melo var. conomon), cvs. Gaucho Redondo, Gaucho Comprido, Redondo Amarelo, Gulfcoast, Chilton, Bonus no. 2, Fantasy; watermelons: cv. Charleston Gray, Progenie da Coreia (Citrullus lanatus); pumpkins: cvs. Mra. Ma, Ornamental, Howden, Mammoth, Kururu, Goianinha (Cucurbita moschata); gourd: Abobora de Porco, cvs. Maranhao, Brasileirinha (Lagenaria siceraria); squash: cv. Pataca Gigante (Cucurbita maxima); cucumber: cvs. Caipira, Branco Meio Comprido, Curumim (Cucumis sativus); loofah: Metro, Semente Branca, Semente Preta (Luffa cylindrica); wax gourd (Benincasa hispida); pumpkin rootstock: Hybrid cv. Keij; snake gourd (Trichosanthes cucumerins) and musk cucumber (Sicana odorifera). To evaluate the resistance, seedlings were transplanted to pots and the root inoculated with 3,000 eggs and second stage juveniles of M. incognita and M. javanica. Fifty days after the inoculation, the plants were evaluated for nematode resistance by means of the reproduction factor. The grafting compatibility between net melon cvs. Bonus no. 2 and Fantasy and the rootstocks previously characterized as resistant were evaluated by means of 60 graftings. CNPH 01-962, CNPH 01-963 and melon 'Gaucho Redondo', were considered resistant to M. incognita. Melon 'Redondo Amarelo', watermelon 'Charleston Gray', watermelon Progenie da Coreia, Trichosanthes cucumerins were considered resistant to M. javanica. Benincasa hispida was resistant to M. javanica and M. incognita. The compatibility between net melons and resistant rootstocks was higher than 98%.

Devido ao severo ataque de nematoides na cultura do meloeiro rendilhado sob ambiente protegido, este trabalho teve por objetivo selecionar porta-enxertos resistentes a Meloidogyne incognita e M. javanica. O experimento foi conduzido em casa de vegetação, de outubro de 2010 a abril de 2011, em Jaboticabal-SP. Foram avaliados 33 porta-enxertos; melões: CNPH 01-930 (Cucumis melo var. flexuosus), CNPH 01-962, CNPH 01-963 (Cucumis melo var. conomon), cvs. Gaúcho Redondo, Gaúcho Comprido, Redondo Amarelo, Gulfcoast, Chilton, Bônus n° 2, Fantasy; melancias: cv. Charleston Gray, Progênie da Coréia (Citrullus lanatus); abóboras: cvs. Mra. Ma, Ornamental, Howden, Mammoth, Kururu, Goianinha (Cucurbita moschata); cabaça: Abóbora de Porco, cvs. Maranhão, Brasileirinha (Lagenaria siceraria); moranga: cv. Pataca Gigante (Cucurbita maxima); pepinos: cvs. Caipira, Branco Meio-Comprido, Curumim (Cucumis sativus); buchas: Metro, Semente Branca, Semente Preta (Luffa cylindrica); abóbora d’água (Benincasa hispida); abó- bora porta-enxerto: Híbrido cv. Keij; quiabo de Metro (Trichosanthes cucumerins) e Cruá (Sicana odorifera). Para avaliar a resistência de plantas, as mudas foram transplantadas para vasos e inoculados com 3.000 ovos e juvenis de M. incognita via sistema radicular. Aos 50 dias após a inoculação, foi realizada avaliação da resistência das plantas, com base no fator de reprodução do nematoide. Foram realizados os mesmos procedimentos para as duas espécies de nematoides. Nos porta-enxertos resistentes aos nematoides foram realizadas enxertias, com os melões rendilhados ‘Bônus n° 2’ e ‘Fantasy’. CNPH 01-962, CNPH 01-963 e melão ‘Gaúcho Redondo’ foram resistentes a M. incognita. Melão ‘Redondo Amarelo’, melancia ‘Charleston Gray’, Progênie da Coréia, e Trichosanthes cucumerins, foram resistentes a M. javanica. Benincasa hispida foi resistente a ambas as espécies. As compatibilidades de enxertia entre os porta-enxertos resistentes e os melões rendilhados ‘Bônus no 2’ e ‘Fantasy’ foram superiores a 98%.
Resistance of cucurbita rootstocks to nematodes and compatibility of grafting with net melon
Keywords: Cucumis melo var. reticulatus; Nematodes; Bonus II; Fantasy; Cucumis melo var. reticulatus; Nematóides; Bônus nº 2; Fantasy